Predictive Autoregressive Integrated Moving Average Model; Meningitis Death and Alzheimer Death - Ogunmola, Adeniyi Oyewole; Onowuzou, James Oruarooghene; Idi, Danjuma (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Nigeria, being a developing country and by its limited resources, priority must be placed on deaths due to ill-health-related research. This study aims to investigate the temporal pattern and forecast mortality associated with Alzheimer’s disease and meningitis using ARIMA model techniques. Results showed that the best fitted for the Alzheimer series is the ARIMA (1, 2, 0) model and the best for the meningitis series is the ARIMA(1,1,0) model. The forecasted values revealed that there will be an inconsistent slight decrease in meningitis deaths while there will be an increase in Alzheimer's deaths over the years. For meningitis, the predicted deaths for 2020, 2021, and 2022 respectively, were 45401, 45216, and 45287, and their 95% confidence intervals were obtained. For Alzheimer's, predicted deaths for 2020, 2021, and 2022 respectively, are 12472, 12832, and 13191, and their corresponding 95% confidence intervals were also obtained. Diagnostic checks for the predictive models were carried out and assumptions were sastisfied.